From Known-Plaintext Security to Chosen-Plaintext Security - Damgård, Ivan B.; Nielsen, Jesper Buus (BRICS Report Series, 2001)
We present a new encryption mode for block ciphers. The mode is efficient and is secure against chosen-plaintext attack (CPA) already if the underlying symmetric cipher is secure against known-plaintext attack (KPA). We prove that known (and widely used) encryption modes as CBC mode and counter mode do not have this property. In particular, we prove that CBC mode using a KPA secure cipher is KPA secure, but need not be CPA secure, and we prove that counter mode using a KPA secure cipher need not be even KPA secure. The analysis is done in a concrete security framework.